Genetic insights into recolonization processes of Mediterranean octocorals - D. Aurelle; J. Tariel; F. Zuberer; A. Haguenauer; C. Ribout; M. Masmoudi; H. Kara; L. Chaoui; J. Garrabou; J.-B. Ledoux; M. C. Gambi (Marine Biology, 2020)

Fine-scale spatial genetic structure in the brooding sea urchin Abatus cordatus suggests vulnerability of the Southern Ocean marine invertebrates facing global change - J.-B. Ledoux; K. Tarnowska; K. Gérard; E. Lhuillier; B. Jacquemin; A. Weydmann; J.-P. Féral; A. Chenuil (Polar Biology, 2012)

From global to local genetic structuring in the red gorgonian Paramuricea clavata : the interplay between oceanographic conditions and limited larval dispersal - K. MOKHTAR‐JAMAÏ; M. PASCUAL; J.‐B. LEDOUX; R. COMA; J.‐P. FÉRAL; J. GARRABOU; D. AURELLE (Molecular Ecology, 2011)
Defining the scale of connectivity among marine populations and identifying the barriers to gene flow are tasks of fundamental importance for understanding the genetic structure of populations and for the design of marine reserves. Here, we investigated the population genetic structure at three spatial scales of the red gorgonian Paramuricea clavata (Cnidaria, Octocorallia), a key species dwelling in the coralligenous assemblages of the Mediterranean Sea. Colonies of P. clavata were collected from 39 locations across the Mediterranean Sea from Morocco to Turkey and analysed using microsatellite loci. Within three regions (Medes, Marseille and North Corsica), sampling was obtained from multiple locations and at different depths. Three different approaches (measures of genetic differentiation, Bayesian clustering and spatially explicit maximum‐difference algorithm) were used to determine the pattern of genetic structure. We identified genetic breaks in the spatial distribution of genetic diversity, which were concordant with oceanographic conditions in the Mediterranean Sea. We revealed a high level of genetic differentiation among populations and a pattern of isolation by distance across the studied area and within the three regions, underlining short effective larval dispersal in this species. We observed genetic differentiation among populations in the same locality dwelling at different depths, which may be explained by local oceanographic conditions and which may allow a process of local adaptation of the populations to their environment. We discuss the implications of our results for the conservation of the species, which is exposed to various threats.

Phylogeography of the red coral (Corallium rubrum): inferences on the evolutionary history of a temperate gorgonian - D. Aurelle; J.-B. Ledoux; C. Rocher; P. Borsa; A. Chenuil; J.-P. Féral (Genetica, 2011)

Mass mortality in Northwestern Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2009)
Late in summer 2003, extensive mass mortality of at least 25 rocky benthic macro‐invertebrate species (mainly gorgonians and sponges) was observed in the entire Northwestern (NW) Mediterranean region, affecting several thousand kilometers of coastline. We were able to characterize the mortality event by studying six areas covering the main regions of the NW Mediterranean basin. The degree of impact on each study area was quantified at 49 sites by estimating the proportion of colonies affected in populations of several gorgonian species compared with reference data obtained in years without mortality signs. According to these data, the western areas (Catalan coast and Balearic Islands) were the least affected, while the central areas (Provence coast and Corsica‐Sardinia) showed a moderate impact. The northernmost and eastern areas (Gulf of Genoa and Gulf of Naples) displayed the highest impact, with almost 80% of gorgonian colonies affected. The heat wave of 2003 in Europe caused an anomalous warming of seawater, which reached the highest temperatures ever recorded in the studied regions, between 1 and 3 °C above the climatic values (mean and maximum). Because this exceptional warming was observed in the depth ranges most affected by the mortality, it seems likely that the 2003 anomalous temperature played a key role in the observed mortality event. A correlation analysis between temperature conditions and degree of impact seems to support this hypothesis. Under the present climate warming trend, new mass mortality events may occur in the near future, possibly driving a major biodiversity crisis in the Mediterranean Sea.

Mass mortality in NW Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2008)

The effects of low dietary levels of DDT on breeding performance in hybrid mice - T. A. Ledoux; J. R. Lodge; R. W. Touchberry; B. Magnus Francis (Archives of Environmental Contamination and Toxicology, 1977)